Adapting to Adversity: Effects of COVID-19 on Parenting in Chile - Pérez, J. Carola; Aldoney, Daniela; Vivanco-Carlevari, Anastassia; Coo, Soledad; Guzmán, Eugenio J.; Silva, Jaime R. (Frontiers in Psychology, 2022)
The pandemic outbreak in March 2020 and its associated sanitary regulations and restrictions triggered an abrupt and significant change for society in general and for families’ organization in particular. In Chile, the Santiago Metropolitan District was under a strict lockdown that involved the closure of the entire educational system. From a systemic-family stress perspective, the impact of these changes might have consequences not only for each individual family member, but for the parental dynamic and, consequently, for children’s well-being. This paper presents the results of a follow-up study showing changes in self-reported parental depression and the perceived home organization of mothers and fathers assessed at three different moments: before the pandemic, at the initial outbreak, and after 1 month of strict lockdown. Relevant moderators were explored using linear mixed models to understand the within-subject changes in mothers’ and fathers’ self-reports across the different assessment times. Financial strain, personality traits of self-criticism and dependency, previous parent–child quality interaction, recent major stressful events, and number of children are highlighted as relevant factors that moderate changes in home chaos and parental mental health perception. Significant risks and protective factors are described for fathers and mothers. The use of pre-pandemic measures as baseline levels enabled the identification of personal and family characteristics that were related to better outcomes. The results help increase our understanding of the sanitary regulations’ impacts on the family system and identify vulnerability indicators that should be considered.